Diagnostic Approach to Monogenic Inflammatory Bowel Disease in Clinical Practice: A Ten-Year Multicentric Experience. Issue 5 (3rd August 2019) - Lega, Sara; Pin, Alessia; Arrigo, Serena; Cifaldi, Cristina; Girardelli, Martina; Bianco, Anna Monica; Malamisura, Monica; Angelino, Giulia; Faraci, Simona; Rea, Francesca; Romeo, Erminia Francesca; Aloi, Marina; et al.
Abstract: Background and aims: Multiple monogenic disorders present as very early onset inflammatory bowel disease (VEO-IBD) or as IBD with severe and atypical features. Establishing a genetic diagnosis may change patients' management and prognosis. In this study, we describe the diagnostic approach to suspected monogenic IBD in a real clinical setting, discussing genetic and phenotypic findings and therapeutic implications of molecular diagnosis. Methods: Information of patients with VEO-IBD and early onset IBD with severe/atypical phenotypes (EO-IBD s/a) managed between 2008–2017 who underwent a genetic workup were collected. Results: Ninety-three patients were included, and 12 (13%) reached a genetic diagnosis. Candidate sequencing (CS) was performed in 47 patients (50%), and next generation sequencing (NGS) was performed in 84 patients (90%). Candidate sequencing had a good diagnostic performance only when guided by clinical features specific for known monogenic diseases, whereas NGS helped finding new causative genetic variants and would have anticipated one monogenic diagnosis (XIAP) and consequent bone marrow transplant (BMT). Patients with monogenic IBD more frequently were male (92% vs 54%; P = 0.02), had extraintestinal findings (100% vs 34%; P < 0.001), and had disease onset ≤1 month of life (25% vs 1%; P = 0.006). Genetic diagnosis impacted patient management in 11 patients (92%), 7 of whom underwent BMT. Conclusion: A genetic diagnosis can be established in a significant proportion of suspected monogenic IBD and has an impact on patients' management. Candidate sequencing may be deployed when clinical findings orientate toward a specific diagnosis. Next generation sequencing should be preferred in patients with nonspecific phenotypes. Abstract : Combining different diagnostic approaches, a genetic diagnosis can be established in 13% of patients with suspected monogenic IBD in clinical practice. Establishing a genetic diagnosis is essential as it impact patients' management and prognosis in most of the patients.